2015
DOI: 10.1016/j.jip.2015.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome sequence and structural characterization of a novel iflavirus isolated from Opsiphanes invirae (Lepidoptera: Nymphalidae)

Abstract: Opsiphanes invirae (Lepidopera: Nymphalidae) is a common pest of the African oil palm tree (Elaeis guineensis) in Brazil. Dead larvae were collected in canopy of oil palm trees cultivated in the amazon region (Para State) and analyzed for viral infection. Electron microscopy of caterpillar extracts showed an icosahedral picorna-like virus particle with 30nm in diameter. Total RNA extracted from partially purified virus particles was sequenced. A contig of 10,083 nucleotides (nt) was identified and showed to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Herein, a novel virus named H. armigera iflavirus ( Carrillo-Tripp et al, 2014;Silva et al, 2015;van Oers, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, a novel virus named H. armigera iflavirus ( Carrillo-Tripp et al, 2014;Silva et al, 2015;van Oers, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…(1) non-enveloped icosahedral particles measuring 30 nm in diameter; (2) genome translation into a polyprotein; (3) the viral coat proteins containing three jelly-roll domains; (4) a three-domain containing a superfamily III helicase, a (cysteine) proteinase with a chymotrypsin-like fold and an RNA-dependent RNA polymerase (RdRp) (Le Gall et al, 2008 (Lanzi et al, 2006), Ectropis obliqua virus , Infectious flacherie virus (Isawa et al, 1998), Lygus lineolaris virus 1 (Perera et al, 2012), Nilaparvata lugens honeydew virus 1 (Murakami et al, 2013), Perina nuda virus (Wu et al, 2002), Sacbrood virus (Ghosh et al, 1999), Slow bee paralysis virus (de Miranda et al, 2010), and Varroa destructor virus 1 (Ongus et al, 2004), although other iflaviruses have been reported (Silva et al, 2015;Suzuki et al, 2015). Herein, we report the nucleotide sequence, genome organization, phylogeny, transmission and tissue distribution of HaIV.…”
Section: Introductionmentioning
confidence: 99%
“…We used TEM to directly confirm the presence of virus particles, first in a sample purified from the in vitro supernatant ( Figure 3B). Iflavirus capsids have been reported to have a diameter of around 30 nanometers (Silva et al, 2015) , and the regular size and shape of viral particles help them stand out by TEM. Indeed, a uranyl acetate negative stain of viral particles collected by ultracentrifugation from the extracellular fraction showed an abundance of symmetric ~30 nm objects, consistent with our expectations for the iflaviridae (Fig 3B).…”
Section: Evidence Of Intracellular and Extracellular Virus In E Muscmentioning
confidence: 99%
“…The iflavirus infection process is still not well understood and seems to differ depending on the host type. In some iflavirus hosts, such as the silkworm Bombyx mori (Himeno et al, 1974), the oil palm tree pest Opsiphanes invirae (Silva et al, 2015), and the honey bee Apis mellifera (Yue et al, 2007), signs of infection are quite evident depending on the virus species and host condition. For example, in silkworm larvae, the pathology of infectious flacherie virus (the type species of iflavirus) infection includes a brown color or other discoloration of the posterior and middle parts of the insect body and flaccidity (Inoue and Ayuzawa, 1972).…”
Section: Introductionmentioning
confidence: 99%